1979
DOI: 10.1159/000181701
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Hematocrit and Erythrocyte Magnesium Concentration in Patients on Regular Hemodialysis

Abstract: Plasma and erythrocyte magnesium (Mg) concentrations were measured in uremics on regular hemodialysis, in healthy persons and in patients with anemia due to causes other than renal failure. The mean plasma Mg concentration was found to be significantly higher in the uremic patients than in other subjects. The erythrocyte Mg concentration in anemic uremics and in nonuremic anemics was found to be higher than in normal subjects and a close inverse relationship was found between this figure and the hematocrit. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Our investigations [12,13] showed that in uremic pa tients on chronic hemodialysis the eMg is inversely corre lated with the hematocrit (Ht) value, and that this behavior of the eMg does not differ from that observed in normal subjects and in nonuremic anemic patients considered as a group. These findings could account for the high eMg found by other authors who probably examined only ure mic patients with low Ht [6,7,30-32], as well as for the wide range of the eMg found by Catto et al [5] who studied patients having a broad range of Ht.…”
Section: Mg Content In Erythrocytes and Tissues Of Uremic Patients Onmentioning
confidence: 62%
See 2 more Smart Citations
“…Our investigations [12,13] showed that in uremic pa tients on chronic hemodialysis the eMg is inversely corre lated with the hematocrit (Ht) value, and that this behavior of the eMg does not differ from that observed in normal subjects and in nonuremic anemic patients considered as a group. These findings could account for the high eMg found by other authors who probably examined only ure mic patients with low Ht [6,7,30-32], as well as for the wide range of the eMg found by Catto et al [5] who studied patients having a broad range of Ht.…”
Section: Mg Content In Erythrocytes and Tissues Of Uremic Patients Onmentioning
confidence: 62%
“…In the uremics of our unit dialyzed with a standard dMg of 0.75 mmol/1 and receiving no Mg-containing drugs, the mean value of sMg was 1.3 ± 0.21 mmol/1, ranging from 0.95 to 1.75 mmol/1 [12,13]. Our previous investigations showed that in chronically dialyzed patients a dMg of 0.25 mmol/1 produces a significant decrease in the sMg as early as 1 month after the beginning of dialysis performed with low dMg [10,11].…”
Section: Serum Mg Concentration (Smg) In Renal Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study it has been shown that in dialyzed uremics the MgT can be calculated directly from the MgP and Ht by the manipulation of the formula concerning the inverse relationship between MgC and Ht [1].…”
Section: Discussionmentioning
confidence: 73%
“…It is worth to be noted that the formula concerning the inverse relationship between MgC and Ht was derived by examining uremics on chronic dialysis with MgP above the normal values [1], however the prediction power of formula 3 was pointed out in dialyzed patients with high and normal MgP. This fact strongly suggests that the pre diction power of the above formula can be valid in any subject, considering that the behavior of the MgC in healthy persons and in nonuremic anemics does not differ from that of uremic patients [I],…”
Section: Discussionmentioning
confidence: 99%